Harmonization of traditional Hindu-Buddhist and Islamic ornaments at the Great Mosque of Demak, Indonesia - Supatmo, Supatmo; Jazuli, Muhammad; Syakir; Syarif, Muhammad Ibnan (Research Journal in Advanced Humanities, 2025)
The Great Mosque of Demak, located in Central Java Province, is a historical milestone legacy of the early spread of Islam in Indonesia (15th century). In addition to being a place of worship, the Great Mosque of Demak is also the center of religious activities for Muslims today. The Great Mosque of Demak has unique ornamental elements. This study aims to find a systematic explanation of the harmonization of the diversity of traditional Hindu-Buddhist and Islamic ornaments at the Great Mosque of Demak. Data was collected using observation, interview, and document tracing methods. The study used a qualitative approach with the iconographic analysis method (pre-iconographical description, iconographical analysis, and iconological interpretation). The results of the study show that the ornamental elements of the Great Mosque of Demak are a combination of Hindu-Buddhist traditional ornaments and Islamic traditional ornaments. Diversity elements of traditional Hindu-Buddhist and Islamic ornaments are harmonized with wisdom so that their values ​​and meanings do not conflict. This wisdom occurs because of the historical background, the process of spreading Islam culturally, and the tolerant attitude of its supporting community.